1993
DOI: 10.1182/blood.v81.12.3435.3435
|View full text |Cite
|
Sign up to set email alerts
|

52Fe for additional marrow ablation before bone marrow transplantation

Abstract: The effectiveness of bone marrow transplantation (BMT) for malignant blood diseases remains limited by the inability of the preparative regimen to eliminate the disease without causing toxicity to normal organs. We have used 52Fe to deliver radiotherapy selectively to the BM. Fourteen patients with hematologic malignancies received 52Fe before a conventional BMT conditioning regimen. The median 52Fe dose was 58 mCi (range, 32 to 85 mCi). As evaluated by quantitative scanning, the median percentage of 52Fe take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The effective dose equivalent was calculated using a simple model according to the International Committee for Radiation Units and Measurements (1979). The effective dose equivalent was found to be <0.5 mSv/MBq and was in accordance with those presented by Ferrant et al (1993). The dose level in our patient studies was considerably below 10 mSv and was found to be at an acceptable level for diagnostic purposes.…”
Section: Methodssupporting
confidence: 91%
“…The effective dose equivalent was calculated using a simple model according to the International Committee for Radiation Units and Measurements (1979). The effective dose equivalent was found to be <0.5 mSv/MBq and was in accordance with those presented by Ferrant et al (1993). The dose level in our patient studies was considerably below 10 mSv and was found to be at an acceptable level for diagnostic purposes.…”
Section: Methodssupporting
confidence: 91%